Pathogenicity in mice of herpes simplex virus type 2 mutants unable to express glycoprotein C. - Johnson, D C (1986)
Herpes simplex virus type 2 (HSV-2) mutants that were unable to express glycoprotein C (gC-2) were isolated. Deletions were made in a cloned copy of the gC-2 gene, and recombinant viruses containing these deletions were screened by using an immunoreactive plaque selection protocol. The viruses did not display a syncytial phenotype. Intravaginal inoculation of BALB/cJ mice with one of the HSV-2 gC-2- viruses produced local inflammation followed by a lethal spread of the viral infection into the nervous system in a manner identical to that produced by parental HSV-2 strain 333. Similarly, intracerebral inoculation of DBA-2 mice with the gC-2- virus produced a lethal neurological disease paralleling that caused by HSV-2 strain 333. These results indicate that gC-2 is not required for the spread of HSV-2 infections in mice.